2009
DOI: 10.1080/00016480903161541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic approaches to idiopathic sudden sensorineural hearing loss and their influence on treatment and outcome

Abstract: Methods:The first 400 patients submitted to the Swedish national database for SSNHL were analyzed. Information was collected at the first visit about the patient's past medical history, potential precipitating events traumata, family medical history, hearing loss, current disease, diagnostic protocol and treatment using questionnaires as well as two audiograms for each patient, one at the first visit to the ENT-clinic and one three months later.Results: 65% of these 400 patients underwent hematological tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
0
13
1
2
Order By: Relevance
“…Thereafter, no improvement may occur . Natural history and placebo‐controlled studies have shown hearing improvement rates of 32% to 65% (average: 46.7%) without treatment, typically within 2 weeks of onset of hearing loss …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, no improvement may occur . Natural history and placebo‐controlled studies have shown hearing improvement rates of 32% to 65% (average: 46.7%) without treatment, typically within 2 weeks of onset of hearing loss …”
Section: Introductionmentioning
confidence: 99%
“…3 Natural history and placebo-controlled studies have shown hearing improvement rates of 32% to 65% (average: 46.7%) without treatment, typically within 2 weeks of onset of hearing loss. [4][5][6][7] Several studies have discussed the presumed prognostic factors of ISSNHL, which include pretreatment demographic characteristics, accompanying symptoms of vertigo or tinnitus, audiogram patterns, treatment methods, and the time elapsed between the onset of hearing loss and the beginning of the treatment. [8][9][10][11][12] Many medical risk factors of ISSNHL have been proposed in the literature, for example, hypertension (HTN), diabetes mellitus (DM), hypercholesterolemia (Hch), cerebrovascular disease (CVD), coronary artery disease (CAD), chronic kidney disease (CKD), and anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden sensorineural hearing loss (SSNHL), commonly known as sudden deafness, can be associated with tinnitus and vertigo and is defined as mostly unilateral decline of hearing function of more than 30 dB in at least three sequential frequencies over 3 days or less ( 1 ). The incidence of SSNHL was reported to range from 3.9 to 27.5 per 100,000 per year and is considered to be an otologic emergency ( 2 4 ). Although some pathophysiological mechanisms have been proposed, the precise cause of SSNHL is still unknown ( 5 ).…”
mentioning
confidence: 99%
“…Diagnosis is one of exclusion: cerebellar infarction, Wallenberg's syndrome or Meniere's disease or a tumor, neurovascular conflict and other issues [1,4,5] have to be ruled out. So far, different diagnostic tests have failed to diagnose VN exactly [6]. According to the inflammation hypothesis, VN may be caused by acute infection with different viruses [7] or by reactivation of latent Herpes virus in the vestibular ganglia [8,9].…”
Section: Introductionmentioning
confidence: 99%